O desenvolvimento da competência clínica e a busca do sujeito pela autonomia em suas interações - Almeida, Luciana Portes de (2021)
ABSTRACT: Clinical competence, understood as the main competence to be developed by the professional nurse, has its own theory proposed by the North American nurse Patricia Benner and is internationally standardized as a descriptor in health sciences (DeCS) in the scientific literature. OBJECTIVE: This study aimed to analyze how an undergraduate nursing course promotes the development of clinical competence in its undergraduates. METHOD: Descriptive exploratory study that used complexity and bricolage as theoretical and methodological references, respectively. The data were produced and analyzed from de mix of three techniques: 1) Documentary analysis of the Pedagogical Course Project; 2) Focus group with nursing students and 3) Semi-structured interview with the course coordinator; and analyzed using bricolage. RESULTS: It is defended the thesis that the development of clinical competence in the nursing undergraduate occurs through the search for the undergraduate subject for autonomy in their interactions, which are: 1) Interpersonal interactions: Teacher, Preceptor and Peers; 2) Interaction with the profession and 3) Interaction with teaching, service and the community. To this end, subjectivity and autonomy are presented as constitutive elements and the basis on which perceptions about clinical competence, its dimensions and its development process are anchored. The recursive relationship between clinical competence and autonomy is defended, which are developed through the tetragram: Practice - Error / uncertainty - Introspection - Self-confidence. Then the development of autonomy in the student's interactions is explored. 1) On Interpersonal Interactions: Teacher, Preceptor and Peers the interaction with the preceptor stands out as the most potent for the development of clinical competence and the use of mimesis / imitation, the articulation between theory and practice and the redefinition of error as powerful strategies for activating the tetragram. 2) The interaction with the profession is reframed during the graduation period, mainly through interactions with the community, with the preceptor and with the service, which, through mimesis / imitation, articulation between theory and practice and stimulating the role of aid, activates the tetragram of development of clinical competence and autonomy. 3) The interaction with teaching, service and community activates the tetragram when it systematically adopts formative assessment, active methodologies, early insertion in the field of practice, curricular internship, stimulating the role of help and the articulation between theory and practice. CONCLUSION: Finally, it concludes by presenting the interactions between the aforementioned interactions, demonstrating that the whole is more than the sum of the parts, that is, the interactions between the interactions are configured as a fundamental element for the performance of clinical competence happens. At the national level, the results of this study may subsidize the processes of construction of Course Pedagogical Projects and discipline plans for undergraduate nursing courses, in addition to assisting teachers who seek ways to purposefully systematize the development of clinical competence in nursing students.